2015
DOI: 10.2147/copd.s83910
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with chronic obstructive pulmonary disease with comorbid bronchiectasis: a systemic review and meta-analysis

Abstract: BackgroundIn the 2014 Global initiative for chronic Obstructive Lung Disease guidelines, bronchiectasis was for the first time defined as a comorbidity of chronic obstructive pulmonary disease (COPD), and this change has been retained in the 2015 update, which emphasizes the influence of bronchiectasis in the natural history of COPD. The present meta-analysis was aimed at summarizing the impact of bronchiectasis on patients with COPD.MethodsDatabases including Embase, PubMed, and the Cochrane Central Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 43 publications
4
70
2
4
Order By: Relevance
“…Several studies [4,5,36,37] demonstrated that gender seemed to have an effect on bronchiectasis occurrence in patients with COPD, and recently, a meta-analysis [38] also showed that COPD patients with bronchiectasis were mostly males. In our study, male gender was shown to be a risk factor for bronchiectasis in patients with moderate–severe COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [4,5,36,37] demonstrated that gender seemed to have an effect on bronchiectasis occurrence in patients with COPD, and recently, a meta-analysis [38] also showed that COPD patients with bronchiectasis were mostly males. In our study, male gender was shown to be a risk factor for bronchiectasis in patients with moderate–severe COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, male gender was shown to be a risk factor for bronchiectasis in patients with moderate–severe COPD. Ni and coworkers [38] suggested that higher smoking rate in males could explain this phenomenon. However, no significant effect of smoking status was found on the presence and extent of bronchiectasis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up study from the same group showed that patients with bronchiectasis and COPD had an increased risk of all‐cause mortality 26. A meta‐analysis of 881 patients, including the above studies in addition to four others, revealed that the coexistence of COPD and bronchiectasis was associated with higher exacerbation rates, degree of inflammatory markers, and rates of Pseudomonas aeruginosa isolation 27. For these reasons, bronchiectasis is now considered a common comorbidity in patients with COPD 21.…”
Section: Pathophysiology Of Ncfbmentioning
confidence: 99%
“…Ni et al including six observational studies with 881 COPD patients, the mean prevalence of bronchiectasis was 54,3% [23]. A study in the UK showed that 29% of patients with COPD followed in primary care had morphological alterations of airway potentially classifiable as bronchiectasis [24].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%